Grande Empresa, Responsabilidade Social e Democracia - Riscado, Priscila Erminia (2013)
The question which guides this thesis is the following: the adoption of a socially responsible attitude combined with accountability redefines the large company's position in the current democratic context? The starting point presented in this paper is that the large company is an actor who skews liberal democracy in the contemporary capitalism. Numerous studies indicate to this direction, signaling how the relationship between in the current democratic environment is increasingly characterized by the dependence of the State the first for the large companies that become key players for guaranteeing jobs and the financing in democratic capitalist societies. For better understand how this relationship between the large company and their main stakeholders develops, the objective here is to see how the phenomenon of corporate social responsibility and the incorporation of accountability among the companies changed or not the meaning of these relationships. The adoption of these attitudes on the part of the company is able to guarantee that they occupy a privileged position in society, the State and the market itself? These aspects are investigated and analyzed in light of the current context and from the already concepts analyzed by political science, such as stakeholders, democracy and accountability